2014
DOI: 10.1038/nrneph.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

Henoch–Schönlein purpura nephritis in children

Abstract: Henoch-Schönlein purpura (HSP) is the most common vasculitis in children, in whom prognosis is mostly dependent upon the severity of renal involvement. Nephritis is observed in about 30% of children with HSP. Renal damage eventually leads to chronic kidney disease in up to 20% of children with HSP nephritis in tertiary care centres, but in less than 5% of unselected patients with HSP, by 20 years after diagnosis. HSP nephritis and IgA nephropathy are related diseases resulting from glomerular deposition of abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
177
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(220 citation statements)
references
References 108 publications
13
177
1
12
Order By: Relevance
“…The prognosis of HSP is mostly dependent upon the severity of renal involvement. 14 In this meta-analysis, we also study the risk of progression of HSP into HSPN, and we found that eNOS G894T and T786C TT gene polymorphism were not associated with the risk of patients with HSP developing into HSPN. However, the number of studies included in this meta-analysis was small, and more studies should be conducted in future.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of HSP is mostly dependent upon the severity of renal involvement. 14 In this meta-analysis, we also study the risk of progression of HSP into HSPN, and we found that eNOS G894T and T786C TT gene polymorphism were not associated with the risk of patients with HSP developing into HSPN. However, the number of studies included in this meta-analysis was small, and more studies should be conducted in future.…”
Section: Discussionmentioning
confidence: 99%
“…These presentations are shown to be predictors of a poor outcome (21). Similar biopsy results at the onset of HSPN have a variable evolution (22), but the significance of the degree of proteinuria for nephritis outcomes has been validated several times (12,17). Still, the unknowns about HSPN pathophysiology make it difficult to find clues from basic research as to which type of treatment is best.…”
Section: Discussionmentioning
confidence: 99%
“…8 Signs in the renal biopsy of IgA vasculitis are the same as those of IgA nephritis. 9 The etiology of IgA vasculitis is yet to be determined; however, there are often precipitating factors, such as infectious diseases, a reaction to drugs or malignancy. 10 It was reported in previous epidemiological studies that the disease was more commonly encountered especially in the autumn and winter months, so upper respiratory tract infections were suspected to be the main triggering factors.…”
Section: Discussionmentioning
confidence: 99%